Pengembangan Media Digital Berbasis Flipbook Untuk Meningkatkan Kemampuan Berpikir Kritis Pada Peserta Didik - Prasasti, Riska Dwi; Anas, Nirwana (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to improve critical thinking skills in students in class IV Mis Al-Furqon Klumpang Kebun in Social Science (IPS) subjects using flipbook media that has been developed. The type of research used is research and development (RnD), which is research used to develop a particular product and test the effectiveness of the product. Media development in this study used the ADDIE research design, which is a development model consisting of five stages including analysis, design, development, implementation, and evaluation. This research develops a product in the form of Flipbook-based digital media on Social Studies subjects which is then tested for feasibility by material experts, media experts, and Class IV students of MIS Al- Furqon Klumpang Kebun. The subjects of this study were 18 fourth grade students. The object of this research is the development of flipbook-based digital media. Based on the results of this research and development, it is concluded that this flipbook-based digital media meets the assessment criteria that have been proven by the material validation score with a score of 3.5 and a media validation score of 4.0 with a recapitulation result of 3.75 which is included in the very valid category. This shows that flipbook-based digital media is included in valid criteria and is suitable for use as teaching materials for teachers and students